2017
DOI: 10.1016/j.lindif.2017.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Time perspective, approaches to learning, and academic achievement in secondary students

Abstract: a b s t r a c t Previous research suggests that both the presence of an extended future time perspective and the generic use of a deep approach to learning predict academic achievement and overall adjustment to school. The present study aimed to investigate how the different dimensions of time perspective (future, present, past, and negative future) influence secondary students' approaches to learning and academic achievement. Participants were 400 students attending the 11th grade (248 girls and 152 boys; Mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 54 publications
(80 reference statements)
2
22
1
2
Order By: Relevance
“…The findings obtained in this research meet the relevant expectations. Some of the findings from this study are similar to those of earlier research results conducted abroad (Byrne et al, 2002;Gow et al, 1994;Janeiro et al, 2017;Liu et al, 2015;Saele et al, 2017). In addition, they are also similar to some domestic research results (Çetin, 2016; Olpak and Korucu 2014).…”
Section: Discussionsupporting
confidence: 91%
“…The findings obtained in this research meet the relevant expectations. Some of the findings from this study are similar to those of earlier research results conducted abroad (Byrne et al, 2002;Gow et al, 1994;Janeiro et al, 2017;Liu et al, 2015;Saele et al, 2017). In addition, they are also similar to some domestic research results (Çetin, 2016; Olpak and Korucu 2014).…”
Section: Discussionsupporting
confidence: 91%
“…FTP. We measured FTP with six future-subscale items from the scale of [68] and on a seven-point Likert-type scale ranging from 1 (never true to me) to 7 (always true to me).…”
Section: Methodsmentioning
confidence: 99%
“…From a motivational perspective, FTP may operate to encourage a person to be purposive and self-regulated and to flourish in the course of academic learning and schooling (Zimbardo and Boyd, 1999;Barber et al, 2009;Janeiro et al, 2017). It is important, in this analysis, for a person to consider a specific future timespan in terms of envisaging different types of endeavors for accomplishment.…”
Section: The Nature Of Future Time Perspective (Ftp)mentioning
confidence: 99%
“…For example, as existing research has shown, the extension of a person’s FTP is closely related to his/her cognition and motivational patterns ( Simons et al, 2004a , b ). Indeed, developments in research over the past seven decades have produced clear and consistent evidence highlighting the significant impact of FTP on different types of adaptive outcomes (e.g., Zimbardo et al, 1997 ; de Bilde et al, 2011 ; Lens et al, 2012 ; Phan, 2015 ; Husman et al, 2016 ; Janeiro et al, 2017 ).…”
Section: The Importance Of Timementioning
confidence: 99%
See 1 more Smart Citation